Fluid-Structure Interaction of a wing (Αλληλεπίδραση πτέρυγας – αέρος) - Markou, George; Papadrakakis, Manolis (My University, 2007)
In this paper a new mesh update technique is proposed combined with a PCG-based algorithm, for the solution of 3D mesh moving boundary problems. The PCG-based algorithm is also applied to three other mesh updating techniques, namely the torsional, the semi-torsional and the ball-vertex spring analogy schemes. The robustness of these four spring analogy methods is evaluated and their computational efficiencies are compared in 3D benchmark problems, including the AGARD wing 445.6 and a 3D three-element airfoil. It is demonstrated that the ortho-semi-torsional spring analogy concept, in conjunction with a PCG type method for the solution of fictitious elasticity problems, provides robustness for substantially distorted meshes and computational efficiency for large scale problems.